PERAN GURU PENDIDIKAN AGAMA KRISTEN DI MASA PASCA PANDEMIC COVID-19 - Vanny Alfrits R. Paendong; Constansia Magrate Adriaanz; Dorkas Alinda Beten; Fardi Lala; Jhon Petrus Malau (Edukasi : Jurnal Pendidikan Agama Kristen, 2021)
Teacher creativity has a big influence on ongoing learning. The danger of learning loss is a challenge for Christian religious education teachers to package learning as interesting and enjoyable as possible for each student. The focus of the problem in this research is the danger of learning loss in the world of education after the Covid-19 pandemic. Researchers used the right method, namely by taking a qualitative approach based on data presented in empirical and descriptive form. As for the results obtained, a teacher who provides fun and digital-based learning will play an important role in the continuity of learning, because here it can prevent the dangers of learning loss.